Design of Greenhouse Prototype Controller and Monitor on Green Mustard Plants - Rozzaq, Ahmad Nur; Harijanto, Alex; Maryani (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2025)
The prototype greenhouse control and monitoring system for green mustard plants is expected to facilitate greenhouse farmers in farming activities. Control and monitoring are carried out on the intensity of incoming sunlight, greenhouse temperature, greenhouse humidity, and soil moisture. The control and monitoring system is carried out by ESP32, BH1750 sensor, DHT22 sensor, and soil moisture sensor. The control process is assisted by an actuator that will turn on and off automatically according to the value limits entered by the greenhouse owner and the readings from the sensor. The control and monitoring device uses Blynk IoT which is connected to an internet of things (IoT) connection. The purpose of this study is to describe the design process of the controller and monitor of the prototype greenhouse for green mustard plants based on the internet of things (IoT) and to find out the results of the controller and monitor of sunlight intensity, air temperature, air humidity, and soil moisture on green mustard plants in the greenhouse. This study uses quantitative descriptive research. The results of this study are the realization of a prototype greenhouse control and monitor for green mustard plants based on the internet of things (IoT) with the main control system being ESP32. The results of the calibration values of the 4 sensor variables are very satisfactory and can be considered as valid tools. The R_square values of the 4 sensor calibrations, namely the BH1750 light sensor, DHT22_1 temperature sensor, DHT22_2 temperature sensor, DHT22_1 humidity sensor, DHT22_2 humidity sensor, and soil moisture sensor are respectively 0.9936; 0.9689; 0.9665; 0.9412; 0.9451; 0.9574.